Penerapan Model Pembelajaran Team Game Tournament Untuk Meningkatkan Motivasi Belajar Siswa Dalam Pelajaran Pkn - Afriza Anggita Devy (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
Learning motivation in learning is very important to note because it is one of the maincomponents. Learning motivation is low because students are not interested or enthusiastic inparticipating in lessons, especially lessons that require a high level of understanding, one ofwhich is Citizenship Education (PKn). In lessons that require a fairly high level ofunderstanding, the teacher should be able to package the learning well so that students do notfeel bored, such as using a fun learning model for students so that learning motivation willincrease and achievement will also increase. One of the fun learning models, especially forCivics Education lessons, is the Team Game Tournament Type Cooperative Learning Model(TGT). This model is suitable for lessons that require students to have a good understandingbecause in this model students are also asked to understand the material but packaged in adifferent way. games so that the material can be remembered by students. A teacher must alsohave creativity and innovation in managing the learning process, for example in applyingsuitable models, methods, and strategies to support the learning process. Especially in lessonsthat require students to become lessons that are considered boring such as Civics so that theteacher's task is to manage the learning process as attractively as possible which makesstudents excited to follow the learning process.